2003
DOI: 10.1002/smj.348
|View full text |Cite
|
Sign up to set email alerts
|

Organizational structure, context, customer orientation, and performance: lessons from Chinese state‐owned enterprises

Abstract: This study develops a model grounded in the contingency theory (i.e., context-structureperformance) applicable to Chinese state-owned enterprises (SOEs). Using data from a sample of 205 industrial SOEs, the study shows that SOE growth performance relative to the industry is positively predicted by formal control, inversely predicted by decentralization, and positively predicted by the interaction of the two. Customer product knowledge utilization, unrelated to growth performance relative to the industry, is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
2
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(184 citation statements)
references
References 49 publications
7
164
2
11
Order By: Relevance
“…Thus, Lin and Germain (2003) observed that growth performance relative to the industry was positively predicted by formal control, inversely predicted by decentralisation, and positively predicted by the interaction of the two. Tan and Peng (2003) found that the relationship between organisational slack and performance was curvilinear, where only a moderate level of slack had a positive effect on performance.…”
Section: Process Of Reform and Change In Chinese Soesmentioning
confidence: 95%
“…Thus, Lin and Germain (2003) observed that growth performance relative to the industry was positively predicted by formal control, inversely predicted by decentralisation, and positively predicted by the interaction of the two. Tan and Peng (2003) found that the relationship between organisational slack and performance was curvilinear, where only a moderate level of slack had a positive effect on performance.…”
Section: Process Of Reform and Change In Chinese Soesmentioning
confidence: 95%
“…Several strategic management scholars have performed specific empirical studies on related topics (e.g. Lin and Germain, 2003;Wolf and Egelhoff, 2002). In this context, Doty et al (1993) explain that organizational design theory has developed from a normative, universalistic approach (promoting 'the best structural form'), via a normative contingency theory approach ('the best structural form exists given specific sets of conditions'), to the notion of equifinity ('in a specific situation, multiple good solutions exist'), Unfortunately, the empirical relevance and rigor of the normative theories has not always been clear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, new employees are oriented about the organization's regulations or are provided with written job descriptions for all positions (Muhammad, 2007). Written documents reveal the organization's high level of formalization (Lin and Germain, 2003). Therefore, clear regulations create a mutual understanding between the organization and the employee, which increases the employee's confidence that they are treated under the same regulation as others.…”
Section: Formalization and Procedural Justicementioning
confidence: 99%